2005
DOI: 10.1002/ejoc.200400688
|View full text |Cite
|
Sign up to set email alerts
|

A Convenient Synthesis of Functionalised 1‐Aryl‐1,3‐alkadiynes

Abstract: A two-step, one-pot synthesis of functionalised 1-arylalka-1,3-diynes is described. A key feature in this approach is exploitation of the "acetylene zipper" reaction to obtain terminal 1,3-alkadiynes 3 from internal isomers 1. Without isolation, but after protonation, the 1,3-alkadiynes 3 are subjected to subsequent Pd/Cu-catalyzed Sonogashira cross-couplings

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…10. A diazotization of o (alka 1,3 diynyl) arylamines 1a-i was carried out with the use of proce dures A-F (Scheme 1), the experimental data are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10. A diazotization of o (alka 1,3 diynyl) arylamines 1a-i was carried out with the use of proce dures A-F (Scheme 1), the experimental data are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…10 Since the cyclization of diacetylenic derivatives of arenediazo nium salts can serve as a one step pathway to 4 halo 3 ethynylcinnolines, the promising building blocks, in particular, for the synthesis of polyfused heterocycles, 11 we continued our efforts in this field. Earlier, we briefly reported that the result of diazotization of o (alka 1,3 diynyl)anilines greatly depends on the reaction conditions and the nature of substituents in the aromatic ring.…”
mentioning
confidence: 99%
“…Compounds 361 were then found to be useful precursors to terminal 1,3-diynes 54 [184][185][186] and unsymmetrically 1,4disubstituted 1,3-diynes 365 184,187 (Scheme 123). Again in 2003, 188 Negishi and coworkers carried out the Sonogashira-type monoalkynylation reaction of 1,1dichloro-1-alkenes 366 under experimental conditions significantly different from those used in the synthesis of compounds 361.…”
Section: Monoalkynylation Reactions Of 11-dihalogenated 1alkenes 31 Monoalkynylation Reactions Of 11-dichloro-1alkenes 182mentioning
confidence: 99%
“…Mesylation of 181 followed by nucleophilic substitution with potassium thioacetate gave thioacetate 182 in 81% yield, which by desilylation and subsequent mesylation of the resulting alcohol provided compound 183 in 87% yield. Finally, simultaneous slow addition of solutions of 183 and sodium methoxide in MeOH via a syringe pump into a large amount of MeOH at room temperature gave the enediyne 184 in 61% yield (Scheme 64).Compound 184 was then converted into isothiochromanone(186) in 58% yield by heating in benzene (2 mM solution) in the presence of 1,4-cyclohexadiene at 80 °C 110. As shown in Scheme 65, the reaction very likely involved the formation of intermediate 185 via the Bergman reaction 90.…”
mentioning
confidence: 99%
“…[7][8][9] The electronic absorption spectra of phenyldiacetylene (phda) derivatives and the effect of solvent on the posi tion and contours of spectral bands have been studied for several years at the Laboratory of Spectrochemistry (De partment of Chemistry, St. Petersburg State University). This work involved the experimental and quantum chemi cal study of the electronic absorption spectra of solu tions of diacetylene derivatives with the general formula H 2 N-Ar-C≡C-C≡C-R ( Fig.…”
mentioning
confidence: 99%